O efeito do programa territorial nas relações sociais dos agricultores familiares do território da cidadania do vale do Rio Vermelho-Go - Camargo, Ricardo de Siqueira (2014)
The Brazilian new rural development paradigm, has led the State to finance territorial-based development initiatives. This thesis aims to understand the effect of the Infrastructure Program (PROINF) in the Vale do Rio Vermelho Territory, in Goiás. The social relationships between of two groups of farmers as well as among the members of the Municipal Council of Sustainable Development (CMDRS) in the municipalities of Itaberaí and Mossamedes was assessed considering the scenarios ex-ante and ex-post PROINF. The outcomes are interpreted based on the social network approach and the concept of social capital. The results reveal that before PROINF there was a low connection between the farmers and that this connection has been improved in the ex-post situation, despite the fact that some farmers remain isolated. The results reveal that the territorial-based policies have empowered farmers by promoting small projects (PROINF) directly targeting the farmers. In contrast, in the municipal councils the connection has not improved even after the implementation of PROINF, implying in the limited effect of the territorial program.